2021
DOI: 10.1177/1934578x21999146
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity and Mechanism of Litsea cubeba L. Essential Oil Against Acinetobacter baumannii

Abstract: The main objective of this study was to investigate the antibacterial activity and mechanism of Litsea cubeba essential oil (LCEO) against Acinetobacter baumannii. The antibacterial activity was examined by a serial dilution method and growth curves. The essential oil showed strong activity against A. baumannii. The mechanism of the antibacterial action was evaluated by the integrity and permeability of the membrane, scanning electron microscopy ( SEM) and SDS-PAGE. The change in permeability of the cell membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 28 publications
1
20
1
Order By: Relevance
“…The third major analyzed component was d-limonene at a concentration of 8.28%, which was lower than in our study, where d-limonene was 14.3%. The opposite ratio of isomers compared to our results was shown in Hao et al [ 26 ], where LCEO extracted from fruit was composed of 29.3% of geranial and 38.3% neral. The d-limonene reached 16.5%, which is approximately a 2% higher percentage than the concentration of d-limonene in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…The third major analyzed component was d-limonene at a concentration of 8.28%, which was lower than in our study, where d-limonene was 14.3%. The opposite ratio of isomers compared to our results was shown in Hao et al [ 26 ], where LCEO extracted from fruit was composed of 29.3% of geranial and 38.3% neral. The d-limonene reached 16.5%, which is approximately a 2% higher percentage than the concentration of d-limonene in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Within the 30 significantly enriched GO terms, there were six terms containing the keyword "membrane". Combined with a recent report [27], LCEO have significant negative effects on the cell membrane and cell wall of A. baumannii 17.…”
Section: Gene Ontology (Go) Functional Enrichment Analysismentioning
confidence: 64%
“…Here, as shown in Figure 11 B, the gene encoding an enzyme (UDP-N-acetylmuramoylalanine--D-glutamate ligase [EC:6.3.2.9]) that catalyzes the irreversible reaction in the early stages of peptidoglycan biosynthesis pathway was up-regulated. A recent report showed that LCEO caused damages to cell membranes of A. baumannii [ 27 ]. Therefore; with some related results above, we think that the cell wall of A. baumannii 17 was damaged by the LCEO, so that the bacteria required more peptidoglycan to do the repair work.…”
Section: Resultsmentioning
confidence: 99%
“…Hu et al, (Hu et al, 2019) reported that methicillin-resistant S. aureus treatment with 1MIC litsea cubeba essential oil after 4 hr, the detection of AKP concentration reduced 77.47%. This may be due to the different sensitivity of the bacteria to each essential oil.…”
Section: Antibacterial Action Of Gne By Cell Wall Damagingmentioning
confidence: 99%
“…The antibacterial mechanism of some nanoemulsion was also demonstrated, such as destroying the cell membrane, leading to intracellular biological macromolecules leakage and affecting the energy metabolism of the cell (Hu et al, 2019;Moghimi et al, 2016).…”
mentioning
confidence: 99%